Competence, Work Motivation, and Work Environment on Job Satisfaction and Teacher Performance at Yayasan Pondok Pesantren Darul Hikmah Koto Baru Kabupaten Dharmasraya - Nur Istiana; Rizaldi Putra; Harry Patuan Panjaitan (Journal of Applied Business and Technology, 2022)
The purpose of this study was to determine the effect of competence, motivation, work environment, and teacher performance on job satisfaction at Darul Hikmah Koto Baru Foundation, Dharmasraya Regency. The method used in collecting data in this research is a questionnaire. The population in this study were all teachers at the Darul Hikmah Koto Baru Foundation, Dharmasraya Regency, with a total of 50 teachers. The sample of this study used the census method with the analysis of the Structural Equation Model (SEM) method with the Partial Least Square (PLS) method. The results showed that performance had a non-significant negative effect on job satisfaction, competence had a positive and non-significant effect on performance and job satisfaction, work environment had a non-significant negative effect on job satisfaction, work environment had a non-significant positive effect on performance, and motivation had a significant positive effect on job satisfaction, and motivation has a non-significant positive effect on teacher performance at Yayasan Pondok Pesantren Darul Hikmah Koto Baru Kabupaten Dharmasraya.